2006
DOI: 10.2466/pms.103.2.427-446
|View full text |Cite
|
Sign up to set email alerts
|

Digit Ratio (2D:4D), Lateral Preferences, and Performance in Fencing

Abstract: The second to fourth digit ratio (2D:4D) is a sexually dimorphic trait (men tend to have lower values than women) and a likely biomarker for the organizational (permanent) effects of prenatal androgens on the human brain and body. Prenatal testosterone, as reflected by 2D:4D, has many extragenital effects, including its relevance for the formation of an efficient cardiovascular system. Previous research, reviewed here, has therefore investigated possible associations of 2D:4D with sport performance. Several st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 36 publications
6
49
1
Order By: Relevance
“…Th e subjects with a right dominant hand had lower right phalangeal, right and left metacarpal and right ray ratios than those with a left dominant hand. As we mentioned before, the association between the digit ratio and HDD was found in several previous studies [21,26,36,39]. However, contrary to our results, these studies demonstrated that left -handed individuals had a lower, more masculine digit ratio.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…Th e subjects with a right dominant hand had lower right phalangeal, right and left metacarpal and right ray ratios than those with a left dominant hand. As we mentioned before, the association between the digit ratio and HDD was found in several previous studies [21,26,36,39]. However, contrary to our results, these studies demonstrated that left -handed individuals had a lower, more masculine digit ratio.…”
Section: Resultscontrasting
confidence: 56%
“…Stoyanov et al [36] found that the diff erence between the right and the left digit ratio was signifi cantly lower in left -handers than in right-handers. Voracek et al [39], in a sample of 54 tournament fencers, found that the right hand digit ratio was signifi cantly lower in left -handed fencers compared to right-handed ones. Nicholls et al [26] in a study of 600 students showed a more masculine pattern of the digit ratio (lower index/ring ratio) in left -handers, a more feminine pattern of the digit ratio in right-handers.…”
mentioning
confidence: 99%
“…It is well known that during intrauterine development the sex steroids have an important organizing effect on the brain with subsequent long-term effects on the behavior (Carlson, 2005;Voracek, Reimer, Ertl, & Dressler, 2006). For that reason many researchers try to find a correlation between 2D:4D and various androgen-dependent or sexually dimorphic aspects of the brain functions and behavior both in healthy persons and among clinical groups (for a review see Hönekopp et al, 2007;Lindová, Hrušková, Pivoňková, Kuběna, & Fleger, 2007;McIntyre, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, some studies (including our own investigation) using the finger length ratio (second to fourth digit) as a biomarker for the prenatal levels of testosterone have shown indirect evidence for a relationship between higher prenatal testosterone and left-handedness [43][44][45][46][47].…”
Section: Handedness-related Differencesmentioning
confidence: 99%